2020
DOI: 10.1002/iub.2277
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulation by microRNAs: Novel insights into osteosarcoma therapy

Abstract: Osteosarcoma (OS) is a kind of primary bone cancer that is considered as the leading cause of children death. Surgery and chemotherapy are considered as common treatment approaches for OS; the rate of survival for patients is almost 60-70%. Besides the used therapeutic approaches, it seems that there is a crucial need to launch new treatments for OS. In this regard, more understanding about cellular and molecular pathways involved in OS can contribute to recovery and develop new therapeutic platforms. Autophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 127 publications
0
32
0
Order By: Relevance
“…Autophagy is an evolutionarily conserved cellular catabolic process that has a critical role in maintaining cellular homeostasis through the lysosomal degradation of unnecessary or dysfunctional components during metabolic stress, pathogenic infection, radiation damage, and drug therapy 37 . Since it has been served in both pro-survival and pro-apoptotic mechanisms, the role of autophagy in cancer cell biology is complicated and evolves throughout tumorigenesis 28 , 30 , 38 , 39 . In this study, TMZ-resistant GBM cell lines showed enhanced autophagic processes, such as increased expression of the autophagy-related gene as well as acidic autolysosome formation after TMZ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an evolutionarily conserved cellular catabolic process that has a critical role in maintaining cellular homeostasis through the lysosomal degradation of unnecessary or dysfunctional components during metabolic stress, pathogenic infection, radiation damage, and drug therapy 37 . Since it has been served in both pro-survival and pro-apoptotic mechanisms, the role of autophagy in cancer cell biology is complicated and evolves throughout tumorigenesis 28 , 30 , 38 , 39 . In this study, TMZ-resistant GBM cell lines showed enhanced autophagic processes, such as increased expression of the autophagy-related gene as well as acidic autolysosome formation after TMZ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Melflufen could also be combined with other novel approaches to eradicate chemo-resistant osteosarcoma. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) comprise a huge part of human genome and are involved in various molecular pathways and processes [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. They are divided into two characteristic groups: house-keeping and regulatory molecules [ 49 ].…”
Section: Micrornasmentioning
confidence: 99%